COVID-19 Prevention Practices Among Prisoners, in Southern Ethiopia - Chea Hankalo N; Alemayehu A; Fikre R; Shona E (Dove Medical Press, 2022)
Nana Chea Hankalo,1 Akalewold Alemayehu,1 Rekiku Fikre,2 Edilu Shona3 1School of Public Health, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia; 2Departments of Midwifery, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia; 3School of Law, College of Law and Governance, Hawassa University, Hawassa, EthiopiaCorrespondence: Nana Chea Hankalo, School of Public Health, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia, Email nanachea@hu.edu.et; cheanana2007@gmail.comBackground: Coronavirus disease-19 (COVID-19) is a highly contagious disease with high attack and case fatality rate. Since WHO's declaration of disease as pandemic in March 2020, the unprecedented global crises have been happening. To curb and reduce such crises, multi-dimensional international efforts have been made, particularly, infection prevention measures has been developed. However, there was a wide gap of implementing COVID-19 prevention measures from rural to urban, from institution to institution and from person to person. Therefore, the aim of this study was to measure the level of prevention practice towards COVID 19 and associated factors in prison, in Sidama National Regional State, Ethiopia.Methods: A cross-sectional study using quantitative method of data collection was conducted in November, 2020 among 422 prisoners in two prisons. Data were collected by trained nurses using structured questionnaires. We analyzed data using SPSS version 24 software. Descriptive statistics and bivariable and multivariable logistic regression analyses were employed to identify factors associated with prevention practices of COVID-19.Results: More than one-fifth (22%; 95% CI: 19%, 26%) of respondents had good preventive practice. Participants who had a history of alcohol intake were 1.79 times less likely to implement good preventive practice for COVID-19 (AOR = 1.79; 95% CI; 1.09, 2.93). The respondents who had negative attitude towards COVID-19 infection were 1.69 times more likely to have poor prevention practice (AOR = 1.69; 95% CI: 1.02, 2.81).Conclusion and Recommendation: In this study, COVID-19 prevention practice among prisoners was very low. Negative attitude and previous alcohol taking history were factors associated with poor prevention practice. Accordingly, the researchers recommends to the concerned body to design educational intervention to change the attitude towards COVID-19 and other infectious diseases and behaviors of the prisoners.Keywords: COVID-19, prevention practice, prison, Sidama, Ethiopia